As percepções dos discentes surdos sobre o ensino superior no âmbito da Universidade Federal de Mato Grosso do Sul: entre o pessoal e o institucional - Lima, Carlos Roberto de Oliveira (2021)
This qualitative study is linked to the Master of the Graduate Program in Education of the Federal University of Mato Grosso do Sul, campus of the Pantanal (UFMS/CPAN) and aims to understand the perceptions of a group of deaf students, the process of subjectivation of these individuals related to the Federal University of Mato Grosso do Sul, Cidade Universitária Campus. As data analysis material, I used two important documents issued by the institution: The Institutional Development Plans from 2010 to 2019 and the Management Reports from 2000 to 2019. Concomitantly with these documents, I conducted a semi-structured interview process with five deaf college students of the campus, of which three are considered a case of student dropout by the Institution and two are regularly enrolled during the research period. The interviews were carried out remotely following the orders of Social Isolation due to the pandemic of the new COVID-19, recorded and transcribed for the composition of the analysis material. The data were analysed in the post-structuralist perspective with the theoretical contribution of Foucault and supported by researchers in the field of Deaf Studies in Education such as Maura Corcini Lopes, Carlos Skliar and Lucyenne Vieira-Machado. The results show that the formation of deaf subjectivities of these students is being developed sometimes based on an auditory social norm that causes tension in the individuals, demanding that they find way to approach the auditory pattern, and sometimes in a linguistic social norm that produces in the target audience a derogatory judgment as people, bringing them, negatively, below the line of “normality” socially established.